2018
DOI: 10.1111/iar.12260
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology, petrogenesis, and tectonic setting of Late Triassic volcanic rocks of the Hadataolegai Formation, central Great Xing'an Range, Northeast China

Abstract: In this study, new geochemical, zircon U–Pb, and Lu–Hf isotopic data are presented for volcanics from the Hadataolegai Formation of the central Great Xing'an Range (GXR) in Northeast China. These new data offer insights into the petrogenesis of the volcanics of the Hadataolegai Formation and the tectonic evolution of the Paleo–Asian Ocean (PAO) and Mongol–Okhotsk Ocean (MOO). These volcanics of the Hadataolegai Formation are divided into andesite‐trachyandesites and dacite‐trachydacites. Zircon U–Pb ages show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…However, given recent high-precision isotopic dating of various units, we propose that the age relationships of the volcanic units require re-evaluation. The Hadataolegai Fm, another volcanic sequence within the CXGR, erupted during the Late Triassic (235-225 Ma; Figure 6a and Table S2; Tang, Sun, Gou, & Yang, 2018;Xu et al, 2017), not during the Early Triassic as previously suggested (IMBGMR, 1996). In this study, we show that the volcanic rocks of the Manketouebo and Manitu formations are Late Jurassic to Early Cretaceous in age, with age ranges from 160 to 135 Ma (peak age at~151 Ma) and 155-120 Ma (peak age at~126 and~131 Ma), respectively (Figure 6b,c; Table S2).…”
Section: Geochronological Framework For Mesozoic Volcanism In the Cgxrmentioning
confidence: 53%
See 2 more Smart Citations
“…However, given recent high-precision isotopic dating of various units, we propose that the age relationships of the volcanic units require re-evaluation. The Hadataolegai Fm, another volcanic sequence within the CXGR, erupted during the Late Triassic (235-225 Ma; Figure 6a and Table S2; Tang, Sun, Gou, & Yang, 2018;Xu et al, 2017), not during the Early Triassic as previously suggested (IMBGMR, 1996). In this study, we show that the volcanic rocks of the Manketouebo and Manitu formations are Late Jurassic to Early Cretaceous in age, with age ranges from 160 to 135 Ma (peak age at~151 Ma) and 155-120 Ma (peak age at~126 and~131 Ma), respectively (Figure 6b,c; Table S2).…”
Section: Geochronological Framework For Mesozoic Volcanism In the Cgxrmentioning
confidence: 53%
“…Recently, “adakite‐like” rocks have been identified from the Hadataolegai Fm (233–226 Ma) in the CGXR. The volcanic rocks of the Hadataolegai Fm do not outcrop parallel to the MO belt, and these rocks originated due to the partial melting of delaminated lower crust and interaction with surrounding mantle material during magma ascent (Tang, Sun, et al, ; Xu et al, ) in an extensional setting associated with the closure of the PAO during the Late Triassic. Moreover, emplacement of A‐type granitoids in the CGXR (236–229 Ma; Ge, Wu, Zhou, & Zhang, ), formation of Mo deposits in the southern GXR, and establishment of the Hongqiling Cu–Ni deposits in the Jilin Province, NE China, occurred within syn‐ and post‐collision tectonic settings that resulted from the closure of the PAO (Jiang et al, ; Jiang, Liang, & Bagas, ; Lü et al, ; Wan et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al, 2011;Zhou, Wilde, Zhao, & Han, 2017; Figure 1a). The CAOB experienced the evolution of the Paleo-Asian Ocean, the Mongol-Okhotsk Ocean, and the Paleo-Pacific Ocean (Dong et al, 2014;Z. Y. Tang, Sun, Gou, & Yang, 2018;J.…”
Section: Introductionmentioning
confidence: 99%